Preclinical Effectiveness of Selective Inhibitor of IRS-1/2 NT157 in Osteosarcoma Cell Lines - Garofalo, Cecilia; Capristo, Mariantonietta; Mancarella, Caterina; Reunevi, Hadas; Picci, Piero; Scotlandi, Katia (Frontiers in Endocrinology, 2015)
Osteosarcoma (OS) is the most common primary bone tumor in children and young adults. Several studies have confirmed the involvement of the IGF system in the regulation of OS cell proliferation and differentiation as well as in the protection of cells from chemotherapy. IRS-1 is a critical mediator of IGF-1R signaling, and we recently reported that its overexpression in OS cells increases proliferation, migration and metastasis both in vitro and in vivo. In this study, we evaluated the efficacy of NT157, a selective inhibitor of IRS-1/2, in a panel of OS cells. A strong dose-dependent inhibition of growth was observed in the MG-63, OS-19, and U-2OS OS cell lines, displaying IC50 values at sub-micromolar doses after 72 h of treatment. Exposure to NT157 elicited dose- and time- dependent decreases in IRS-1 levels. Moreover, a protein analysis showed that the degradation of IRS-1 inhibited the activation of principal downstream mediators of the IGF pathway. NT157 significantly affected the cells’ migratory ability, as confirmed by a wound-healing assay. The inhibitor induced cytostatic effects, as evidenced by G2/M cell cycle arrest, and did not affect apoptosis. Consequently, NT157 was combined with drugs used to treat OS in order to capitalize on its therapeutic potential. Simultaneous treatments were made in association with chemotherapeutic agents in a fixed ratio for 72 h and cell proliferation was determined by MTT assay. Synergistic or addictive effects with respect to single agents are expressed as the combination index (CI). Significant synergistic effects were obtained with several targeted drugs, such as Everolimus, an mTOR inhibitor, and NVP-BEZ235, a dual inhibitor of PI3K/mTOR. Overall, these findings provide evidence for the effectiveness of a selected inhibitor of IRS1/2 NT157 in OS cells, displaying a promising approach based on the targeting of IRS-1 combined with other therapies for the treatment of this pediatric solid tumor.